Respuesta :
The change in the temperature is proportional to the difference in temperatures. Let's call the initial temperature of the room and the thermometer [tex]E_0[/tex] and the current temperature [tex]E(t)[/tex] where [tex]t[/tex] is the elapsed time in minutes. The outside temperature is 20 F.
Newton's Law of Cooling:
[tex]E(t) - 20 = (E_0 - 20) e^{- k t}[/tex]
We're given [tex]E(1)=70 \textrm{ and } E(5)=45[/tex]
[tex]70-20 = (E_0 - 20) e^{-k}[/tex]
[tex]45-20 =(E_0 - 20) e^{-5k}[/tex]
Dividing,
[tex]\dfrac{50}{25}=e^{4k}[/tex]
[tex]k = \dfrac 1 4 \ln 2 [/tex]
Now,
[tex]E(t) - 20 = (E_0 - 20) e^{- k t}[/tex]
[tex]E_0 = 20 + (E(t) - 20)e^{k t}[/tex]
[tex]E_0 = 20 + (E(1) - 20)e^{k}[/tex]
[tex]E_0 = 20 + (70 - 20)e^{\ln 2/4}[/tex]
[tex]E_0 = 20 + 50 \cdot 2^{1/4} \approx 79.46 \textrm{ degrees F} [/tex]
Using the Newton's law of cooling principle, the initial temperature of the inside room would be 79.44°F
According to the Newton's Law of Cooling :
- [tex]T(t) = T_{s} + (T_{o} - T_{s})e^{-kt} [/tex]
- Temperature at a given time, t = 5 minutes = 45°
The equation can be expressed thus :
[tex]\deltaT (T_{o} - T_{s})e^{-kt} [/tex]
[tex]70 - 20 = (T_{o} - 20)e^{-k} [/tex]
[tex]70 - 45 = (T_{o} - 20)e^{-5k} [/tex]
[tex] 50 = (T_{o} - 20)e^{-k} [/tex] - - - (1)
[tex] 25 = (T_{o} - 20)e^{-5k} [/tex] - - - - (2)
Divide (1) and (2) - - -
[tex]\frac{50}{25} = e^{-k + 5k} [/tex]
[tex]\frac{50}{25} = e^{4kt} [/tex]
[tex] 2 = e^{4kt} [/tex]
Take the ln
[tex] In 2 = 4k [/tex]
k = 0.173
The initial temperature is defined thus :
[tex]T(o) = T_{s} + (T_{t} - T_{s})e^{kt} [/tex]
[tex]T(o) = 20 + (70 - 20)e^{0.173(1)} [/tex]
[tex]T(o) = 20 + (50 \times 1.1888) = 79.44°F[/tex]
Therefore, the initial temperature is 79.44°F
Learn more :https://brainly.com/question/2160360